IMPROVING LONG JUMP ABILITY LEARNING OUTCOMES THROUGH A CONSTRUCTIVIST APPROACH: IMPROVING LONG JUMP ABILITY LEARNING OUTCOMES THROUGH A CONSTRUCTIVIST APPROACH - Karim, Achmad (MACCA : Science-Edu Journal, 2025)
This study aims to describe the planning, action, observation, reflection and implementation of the Constructivism Learning Approach in an Effort to Improve the Learning Outcomes of Long Jump Ability of Grade IV Students of SDN Labuang Baji, Makassar City. This study is a Classroom Action Research which was carried out in 4 Meetings in Cycle I and Cycle II and was designed through four stages, namely Planning, Implementation, Observation and Reflection. The data of this study are the results of learning long jump. The data source of this study was 40 grade IV students of SDN Labuang Baji, Makassar City. The collection of long jump learning outcomes data was carried out by providing practice questions, and using long jump motion process assessment sheets and observing student attitudes and behavior through worksheets in Cycle I and Cycle II. The collected data were analyzed quantitatively and qualitatively. The results of the quantitative analysis of long jump learning outcome data showed that the number of students who completed Cycle I was 21 people with a percentage of 52.5% and the number of students who completed Cycle II was 39 people with a percentage of 97.5%. Based on the results of this study, it can be concluded that physical education learning through the Constructivist Learning Approach can improve the learning outcomes of long jump abilities of grade IV students at SDN Labuang Baji, Makassar City.